Dependency of Exercise‐Induced T‐Wave Alternans Predictive Power for the Occurrence of Ventricular Arrhythmias from Heart Rate. Issue 4 (4th November 2014) - Burattini, Laura; Man, Sumche; Fioretti, Sandro; Di Nardo, *† Francesco; Swenne, Cees A.
<x xml:space="preserve">Abstract</x> Background T‐wave alternans (TWA) is a noninvasive index of risk for the occurrence of ventricular arrhythmias. It is known that TWA amplitude (TWAA) increases with heart rate (HR) but how the TWA predictive power varies with HR remains unknown. Thus, the aim of this study was to evaluate the dependency of exercise‐induced TWA predictive power for the occurrence of ventricular arrhythmias from HR. Methods TWA was identified using our HR adaptive match filter in exercise ECGs from 248 patients with implanted cardiac defibrillator (ICD), of which 72 developed ventricular tachycardia and/or fibrillation during the 4 year follow‐up (ICD_Cases) and 176 did not (ICD_Controls). TWA predictive power was evaluated at HRs from 80 to 120 bpm by computing the area under the receiver operating characteristic curve (AUC) obtained using the maximum TWAA (maxTWAA) and the TWAA ratio (TWAAratio; i.e., the ratio between TWAA at a specific HR and at 80 bpm). Results TWAA increased with HR. At 80 bpm maxTWAA was lower than at 120 bpm in both ICD_Cases (22 μV vs 41 μV; P < 10−2) and ICD_ Controls (16 μV vs 36 μV; P < 10−4). However, only at 80 bpm ICD_Cases showed significantly higher maxTWAA than ICD_Controls (AUC = 0.6486; P = 0.0080). TWAAratio was higher in ICD_Controls than ICD_Cases for all HR but 120 bpm, and its predictive power was maximum at 115 bpm (AUC = 0.6914; P < 0.05). Conclusions Exercise‐induced TWA predictive power for the occurrence of ventricular arrhythmias, quantified using both maxTWAA and TWAAratio, was higher at low rather than at high HR.